Petroglifi iz Jame v bližini Trnovskega studenca nad Ilirsko Bistrico na Snežniški planoti - Hrobat Virloget, Katja (Studia mythologica Slavica, 2014)
The article is an attempt of interpretation of the petroglyphs in Cave in the vicinity of Trnovo spring or Iapods' cave. The anthropomorphic figure (archer/horseman) and the circles with the crossed lines inside are compared to other cases of rock art. A step forward of the analysis is the comparative study of ritual caves with phallic stalactites in the sur - roundings and the analysis of its mythical landscape.
Keywords: kapniki; petroglyphs; phallic stalactite; jame; Jame, Slunj; arheološka najdišča; ritual caves; Trnovski studenec; mythical landscape; petroglifi; Snežniška planota; mythology; mitologija; simbolika; ljudska verovanja